When Deportation Is a Death Sentence - Sahaidak, Viktoriia; Grigolishvili, Mariam (Vilnius University Open Series, 2024)
The research concerns the widespread distribution of deportation cases across the globe and the continued use of death penalties in numerous states. By exploring the cultural, ethical, and legal sides of this complicated issue, this thorough analysis seeks to highlight their numerous aspects and tasks` set. The article provides an advanced knowledge of the broad consequences, difficulties, and moral issues involved in these matters through extensive research and a wide range of views. Major concerns regarding fairness are raised by the widespread use of collective expulsion in deportation proceedings. In order to advocate for a fair and just decision that takes into account the individual circumstances of each person involved in the deportation process, it is crucial to emphasize the importance of performing individual assessments for each case.
Keywords: deportation; death sentence; genocide; death penalty; non-refoulement principle